Tech[no]logical Space: - Greenberg, Stephanie (My University, 2019)
Technology has been an underpinning determinant that has perpetuated society’s cycle of disruption, disrupting the typical logic surrounding the use and perception of space. The reduction of physical spatial barriers, caused by the full enablement of digital culture and technology, has diminished both physical and social interactions. This has resulted in local fragmentation and a global connection . It has also caused acceleration in the temporal dimension, resulting in a ‘sped-up’ lifestyle. These forms of acceleration and propagation of the virtual realm have not only compressed the time in which we perceive reality but have also disrupted society’s normative understanding of space. This new propagation of space, along with the advancement of disruptive technology, has propelled architecture into a new realm of experimentalism; thereby, advocating for the enablement and translation of the disruption caused by both digital and augmented culture into architecture. Situated in and focusing on Rosebank, this thesis will explore architecture’s role as a mediator for disruptive technologies. The building will respond to the spatial transformation and societal disconnection created by ‘disruptive’ technologies through the utilisation of nature and the transformation of speculated ‘left-over-space’. Thus, through the demolition and design intervention of an existing parking structure, it will propose a co-sharing work pavilion. The design intends to facilitate the socialisation and collaboration of the mobile workforce with the natural environment. Through the emphasis of the natural world, the social world and the human body, the building will explore new spatial perceptions. These perceptions will no longer be centred around the physical aspect of space, but instead on human experience. Society’s complete immersion of technology into everyday practice, has made its implications unavoidable. Therefore, it is continuously changing the way society interacts with each other, nature and the built environments. The pervasive nature of technology encourages architects to start designing in anticipation of the future. As a platform for the disruption caused by technological innovation, the design and discourse act as respondents and enablers of technology. They also use nature as a method to disturb the disruption caused by technological innovation - through its ability to restore diminished relationships between society, nature and technology. This, therefore, speculates on an alternative environment and future for architecture in the workforce and, to a greater extent, society.
This document is submitted in partial fulfilment for the degree: Master of Architecture (Professional) at the University of the Witwatersrand, Johannesburg, South Africa, 2018.
Keywords: Architecture and technology; Architecture--Technological innovations; Architecture, Modern--21st century